2001
DOI: 10.1034/j.1399-3089.2001.00176.x
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric analysis of miniature swine hearts as potential human xenografts

Abstract: Miniature swine are considered to be potential donors for clinical cardiac transplantation. However, it is unclear how an appropriately sized porcine donor will be selected for a particular human recipient. To address this issue, we performed a morphometric study of the swine heart using transthoracic echocardiography (n = 26) to determine the diameters of the aortic annulus and root, pulmonary artery annulus, and mitral valve annulus. We also obtained direct ex vivo measurements of swine heart weight and line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 5 publications
1
17
0
Order By: Relevance
“…This technique takes into consideration the rheometry of blood in this particular anatomic area. The diameters of the conduits were similar to those of the superior and the inferior vena cavae [18]. Furthermore, with this technique anastomoses were performed by suturing the graft to the caval veins, rather than inserting the graft intraluminally [13,16].…”
Section: Discussionmentioning
confidence: 99%
“…This technique takes into consideration the rheometry of blood in this particular anatomic area. The diameters of the conduits were similar to those of the superior and the inferior vena cavae [18]. Furthermore, with this technique anastomoses were performed by suturing the graft to the caval veins, rather than inserting the graft intraluminally [13,16].…”
Section: Discussionmentioning
confidence: 99%
“…To estimate the proportions of the porcine heart beforehand, the published correlations between porcine cardiac morphology and parameters easy to measure from the outside view will help in donor selection. Allan et al [24] demonstrated that pigs' body weight strongly correlates with the their heart weight, length, width, and depth. The diameters of the aortic root and the main pulmonary artery correlate with the pigs' length.…”
Section: Discussionmentioning
confidence: 99%
“…To adjust the alternans voltage threshold to a level suitable for the anesthetized swine, we scaled the human alternans voltage threshold by the ratio of the mass of the average 40 kg swine heart, 177 g 41 , to the mass of the average human heart, 320 g (0.55). We accordingly implemented a swine body surface alternans voltage threshold of 0.55 μV.…”
Section: Methodsmentioning
confidence: 99%